Field‐evolved resistance to 11 insecticides and the mechanisms involved in Helicoverpa armigera (Lepidoptera: Noctuidae). Issue 11 (22nd July 2021) - Wang, Qinqin; Rui, Changhui; Wang, Li; Nahiyoon, Shahzad Ali; Huang, Weiling; Zhu, Junshu; Ji, Xuejiao; Yang, Qingjie; Yuan, Huizhu; Cui, Li
Abstract: BACKGROUND: To understand the ongoing resistance of cotton bollworm, Helicoverpa armigera, the sensitivity of five field populations to commonly used insecticides, indoxacarb, abamectin, methoxyfenozide, chlorfenapyr, chlorantraniliprole, spinetoram, lambda‐cyhalothrin, carbosulfan, metaflumizone, chlorpyrifos, and flufenoxuron, were evaluated. Furthermore, the biochemical and molecular mechanisms of field‐evolved resistance in H. armigera were also investigated. RESULTS: Five field populations of H. armigera showed moderate resistance to indoxacarb, chlorantraniliprole, metaflumizone, methoxyfenozide, carbosulfan and lambda‐cyhalothrin. The resistance ratio (RR) of indoxacarb was significantly correlated with glutathione‐S‐transferases (GSTs) activity ( r  = 0.913, P  = 0.011). Methoxyfenozide RR was largely correlated with cytochrome P450s activity ( r  = 0.860, P  = 0.028). Besides, six cytochrome P450s genes of CYP4L5 in AQP, CYP6B7 and CYP9A14 in HDP and BDP, CYP9A17V2 in HDP and YSP, CYP332A1 in HDP, LFP, AQP and YSP, CYP337B1 in YSP, and two GSTs genes of GSTd1 and GSTs1 in HDP were overexpressed (>5‐fold). Moreover, indoxacarb RR was positively correlated with the overexpression of GSTs1, GSTd1 and CYP9A14 genes ( r  = 0.880, 0.98 and 0.86, P  = 0.021, 0.001 and 0.028, respectively). The transcript of CYP9A17V2 and CYP337B1 were found to be correlated with metaflumizone RR ( r  = 0.950, P  = 0.004) and carbosulfan RR ( r  = 0.850, P  = 0.033), respectively. CONCLUSION: H. armigera can be effectively controlled using abamectin, chlorfenapyr, chlorpyrifos and spinetoram in Hebei and Shandong provinces. The present study demonstrated that the relative expression level of GSTs1, GSTd1, CYP9A14, CYP9A17V2 and CYP337B1 genes were significantly correlated with the resistance ratio to indoxacarb, metaflumizone and carbosulfan in field H. armigera . Abstract : H. armigera can be effectively controlled using abamectin, chlorfenapyr, chlorpyrifos and spinetoram in Hebei and Shandong provinces. The present study demonstrated that the relative expression level of GSTs1, GSTd1, CYP9A14, CYP9A17V2 and CYP337B1 genes were significantly correlated with the resistance ratio to indoxacarb, metaflumizone and carbosulfan in field H. armigera . © 2021 Society of Chemical Industry.